THU0450 Hospital readmissions for gout in the united states: a national database study. (15th June 2017) - Annapureddy, N; Saha, A; Poojary, P; Chauhan, K; Nadkarni, G
Abstract : Background: Gout is associated with significant burden and risk of readmission. Little is known about readmissions among Gout patients on a national level in the United States. Objectives: The aim of this study was to describe unplanned hospital readmission rates among adult gout patients and assess predictors of readmission. Methods: We analyzed the 2013 National Readmission Database (NRD) to quantify readmission rates among Gout patients. The NRD includes weighted discharge data from 21 geographically diverse states accounting for 49.3% of the U.S. population. It includes approximately 14 million un-weighted discharges (49.1% of all U.S. discharges) corresponding to 36 million annual discharges nationwide. NRD data is from patients with non-Medicare payers (Medicaid, private, self-pay, or other). Gout hospitalizations were identified using the International Classification of Diseases, ninth Revisions, Clinical Modification (ICD-9-CM) diagnosis code 274.0x. All hospitalizations for patients age ≥18 were included. In efforts to exclude routine readmissions, we excluded those admissions related to pregnancy, those for chemotherapy, admissions where the patient was readmitted the same day as they were discharged, who had deaths during the same index hospitalizations, hospitalizations for less than 24 hours, and those with missing discharge. We utilized Chi-square tests, t tests and Wilcoxon rank-sum tests as appropriate. Survey logistic regression was used to assess the relationship between potential predictors for readmissions and the odds of at least one 30-day unplanned readmission. This analysis was chosen given the NRD data, which involves nested, weighted observations that are inherently stratified in clusters to produce national estimates. Results: A total of 10708 index hospitalizations which had Gout as the primary diagnosis were included in the analysis. Among those with a primary Gout diagnosis, there were 1212 30-days readmissions (11.3%). 14.3% percent of patients with Gout as the primary diagnosis on index hospitalization were readmitted with the same diagnosis. The next most common readmission diagnoses were congestive heart failure (CHF), septicemia, and acute and unspecified renal failure (Figure 1 A). In multivariable analysis of index hospitalizations with Gout as the primary diagnosis, CHF (OR 1.25, 95% CI, 1.05–166), chronic kidney disease (CKD) (OR 1.54, 95% CI, 1.23–1.92), atrial fibrillation (AF) (OR 1.33, 95% CI, 1.10–1.78), deep venous thrombosis (DVT) (OR 1.29, 95% CI, 1.03–1.88), APR-DRG severity level 3 and 4 (OR 1.51, 95% CI, 1.01–2.38 and OR 2.10, 95% CI, 1.06–4.58), discharge to specialized care (OR 1.47, 95% CI, 1.07–2.02), discharge to home health care (OR 1.35, 95% CI, 1.03–1.77), and discharge against medical advice (OR 3.85, 95% CI, 1.50–9.91), were significantly associated with 30-days readmission after adjusting for demographics, comorbidities, hospital characteristics, payer type, and the APR-DRG severity scale (Figure 1 B). Conclusions: In a national readmissions database, 11.3% of patients admitted with a primary diagnosis of Gout were readmitted within 30 days. Significant predictors of readmission included CHF, CKD, AF, APR-DRG severity level 3 or 4 and any discharge other than routine. Disclosure of Interest: None declared